Skeletfundet ved Vædebro - Jensen, Per Lysdahl (Kuml, 1967)
Summary The results of an anthropological examination of the skeletal remains from the Roman Iron Age found at Vædebro in Jutland are reported. Remains from 18 persons are recognised, of these at least 15 young to middle-aged men with several lesions in skulls and extremities. It is concluded that the individuals were killed in battle. Ole Christensen